PERAN GURU AGAMA ISLAM DALAM MEMBENTUK KARAKTER ISLAMI GENERASI Z di SMK NEGERI 1 KERTAK HANYAR - Anis Ridha Wardati; Auliya Fathul Jannah (STAI AL FALAH Banjarbaru, 2026)
The formation of Islamic character among Generation Z has become a significant concern in contemporary education, particularly amid rapid digital technological advancement and globalization. Islamic Religious Education (PAI) teachers hold a strategic position in fostering students’ Islamic character at the secondary school level. This study aims to analyze the role of Islamic Religious Education teachers in shaping the Islamic character of Generation Z students at SMK Negeri 1 Kertak Hanyar. The research employed a qualitative approach with a field research design. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that Islamic Religious Education teachers perform multiple roles as educators, instructors, mentors, trainers, advisors, and role models in the process of character formation. Despite challenges such as students’ limited engagement in religious learning and the influence of social media, teachers consistently apply relevant and contextual instructional strategies to ensure that Islamic values are internalized and practiced in students’ daily lives.